MiR-208b/miR-21 Promotes the Progression of Cardiac Fibrosis Through the Activation of the TGF-β1/Smad-3 Signaling Pathway: An in vitro and in vivo Study - Zhang, Yifan; Yuan, Bo; Xu, Yue; Zhou, Na; Zhang, Ruiqi; Lu, Lan; Feng, Zhanbin (Frontiers in Cardiovascular Medicine, 2022)
Background: Regulatory molecules microRNAs (miRNAs) have been implicated in myocardial fibrosis. However, the specific mechanism by which they lead to myocardial fibrosis remains unclear. This study aimed to explore the roles of miR-208b, miR-21 and transforming growth factor-β1 (TGF-β1)/Smad-3 signaling pathway components in cardiac fibrosis development. Methods: Thirty-six consecutive acute myocardial infarction (AMI) patients were included in this study. Plasma was collected on admission and at 24 h, 48 h and 6 d. The levels of plasma miR-208b, miR-21, TGF-β1 and Smad-3 were measured using reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and cardiac calcium protein T (cTnT) and creatine kinase isoenzyme (CK-MB) were detected by electrochemiluminescence analysis. H9C2 cells were exposed to hypoxia and divided into 4 groups (hypoxia treatment for 6 h, 24 h, 48 h and 72 h). These stimulated cells were then transfected with miRNA inhibitors and mimics for gene overexpression and inhibition. RT-qPCR was used to detect the expression of miR‑208b, miR-21, TGF-β1 and Smad-3, and western blot analysis was used to detect TGF-β1 and Smad-3 protein expression. Results: The plasma analysis showed cTnT and CK-MB expression peaks 24 h after symptom onset; miR-208b, miR-21, TGF-β1 and Smad-3 levels showed no peak and increased gradually with time. Cell experiments revealed that miR-208b and TGF-β1 were upregulated elevated along with increased hypoxia exposure; miR-21 expression peaked at 24 h and 72 h, with the highest peak at 72 h, and Smad-3 expression peaked at 6 h and 72 h, with the highest peak at 72 h. miR-208b and miR‑21 expression was positively correlated with TGF-β/Smad-3 expression. TGF-β1/Smad-3 mRNA and protein levels were elevated in the miR-208b and miR-21 overexpression groups and reduced in the miR-208b and miR-21 inhibition groups. Conclusions: miR-208b and miR-21 promote cardiac fibrosis progression through TGF-β1/Smad-3 signaling pathway activation.